1989
DOI: 10.1073/pnas.86.7.2438
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the migration stimulating factor produced by fetal and breast cancer patient fibroblasts.

Abstract: We have previously shown that (i) human skin fibroblasts of fetal and adult origin display distinctive migratory phenotypes, (ii) this difference in cell behavior results from the production of a soluble "migration stimulating factor" (MSF) by fetal cells, and (iii) skin fibroblasts from breast cancer patients commonly resemble fetal fibroblasts both in migratory phenotype and in production of MSF. Data are now presented indicating that MSF present in the conditioned medium of fetal and cancer patient fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
61
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(64 citation statements)
references
References 27 publications
2
61
0
1
Order By: Relevance
“…19 For example, they may develop smooth muscle differentiation (myofibroblasts) 27 with increased motility into collagen gel 28 and soluble migration stimulation factor (MSF) secretion. 29 A recent study even showed that normal-appearing stromal cells within breast cancer tissues underwent loss of heterozygosity (LOH) in several loci, whereas no LOH was observed in the stromal cells from reduction mammoplasty (without cancer). 30 These tumor-associated fibroblasts have been designated by some investigators as "activated," 31 "abnormal" 29 or "reactive" 32 in malignant breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…19 For example, they may develop smooth muscle differentiation (myofibroblasts) 27 with increased motility into collagen gel 28 and soluble migration stimulation factor (MSF) secretion. 29 A recent study even showed that normal-appearing stromal cells within breast cancer tissues underwent loss of heterozygosity (LOH) in several loci, whereas no LOH was observed in the stromal cells from reduction mammoplasty (without cancer). 30 These tumor-associated fibroblasts have been designated by some investigators as "activated," 31 "abnormal" 29 or "reactive" 32 in malignant breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is able to stimulate fibroblast migration in a native collagen-I matrix. 12,13 We provide the first evidence that MSF displays constitutive Fn-proteinase activity. We show that several human breast adenocarcinoma cell lines constitutively express MSF and have an endogenous Fn-proteinase activity.…”
mentioning
confidence: 84%
“…Several investigators reported that stromal alterations precede the malignant progression of tumor cells, 4,5 and that local and mutual interactions between cancer cells and stromal cells, such as fibroblasts, macrophages, lymphocytes, neutrophils, and endothelial cells, are important for regulating the extracellular matrix degradation, angiogenesis, and migration and invasion of tumor cells. 6 Concerning cancer-stromal interaction in oral SCC, Matsumoto et al 7 and Sugiura et al 8 reported that gingival fibroblasts markedly enhanced the invasion of oral SCC cells in vitro.…”
mentioning
confidence: 99%